1994
DOI: 10.1128/mcb.14.1.128-137.1994
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear factor YY1 participates in repression of the beta-casein gene promoter in mammary epithelial cells and is counteracted by mammary gland factor during lactogenic hormone induction

Abstract: Expression of the beta-casein milk protein gene in the mammary epithelial cell line HC11 is primarily regulated at the transcriptional level. A 338-bp segment of promoter sequence 5' of the transcription start site is sufficient to confer inducibility by the lactogenic hormones insulin, glucocorticoid hormone, and prolactin. Positively and negatively acting promoter elements and specific DNA binding proteins have been identified. The binding of the mammary gland factor MGF to a site between -80 and -100 is ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
1
1
0
1
Order By: Relevance
“…Thus, these results indicated that complex A is a multiprotein complex and YY1 is one of the protein components. As no band was revealed by the UV crosslinking analysis of the B complex (data not shown), and its mobility in EMSA is similar to that of a previously reported derivative derived from protease digestion of a YYl complex [35], our data also suggests that the B complex may be a derivative of the A complex.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, these results indicated that complex A is a multiprotein complex and YY1 is one of the protein components. As no band was revealed by the UV crosslinking analysis of the B complex (data not shown), and its mobility in EMSA is similar to that of a previously reported derivative derived from protease digestion of a YYl complex [35], our data also suggests that the B complex may be a derivative of the A complex.…”
Section: Discussionsupporting
confidence: 88%
“…These CoRE units are defined as a cluster of transcription factor binding sites containing both positive and negative regulatory elements which integrate signal transduction pathways through protein‐DNA and protein‐protein interactions (Jiang and Levine 1993). The primary factors associated with activation of the β‐casein CoRE include signal transducer and activator of transcription 5 (Stat5), glucocorticoid receptor (GR), and CCAAT enhancer binding protein β (C/EBPβ), while Yin Yang‐1 (YY‐1) associates with the CoRE as a negative regulator of gene expression (Schmitt‐Ney et al 1991; Meier and Groner 1994; Raught et al 1994; Wakao et al 1994; Doppler et al 1995; Raught et al 1995; Lechner et al 1997; Seagroves et al 1998). Interestingly, none of the transcription factors associated with the β‐casein CoRE is mammary gland‐specific or even restricted to the lactation phase of development.…”
Section: Regulation Of Milk Protein Gene Expressionmentioning
confidence: 99%
“…L'analyse des séquences des régions régulatrices utilisées dans les expériences mentionnées ci-dessus montre que ces régions ne portent pas que des éléments potentiels de fixation pour Stat5. De nombreuses autres séquences consensus susceptibles d'interagir notamment avec les diverses formes de NF1 (Li & Rosen, 1995 ;Mukhopadhyay et al, 2001) d'ets (Galang et al, 2004Mcknight et al, 1995 ;Welte et al, 1994), de C/EBP ) ou de YY1 (Meier & Groner, 1994) sont présentes et s'étendent jusque 7 kb en amont du site d'initiation de la transcription. Les régions régulatrices de ces gènes sont donc composées de nombreux éléments de réponse et ont été baptisées "Complexe responsive elements" (CoRE) (Rosen et al, 1999).…”
Section: Ces Régions Portent D'autres éLéments Régulateursunclassified